A cerâmica campaniense do acampamento romano da Lomba do Canho (Arganil) - Fabião, Carlos (2017)
This paper deals with the campanian ware collected from the excavations made in the roman camp Lomba do Canho (Arganil) since 1956 to 1983. It is the tipical homogeneous sample of the B circle produtions of the middle I century BC (F 2230/2280; F 2300 and F 7500). The other roman artifacts from the site, such as coins, lamps, amphorae, ensure a setting and an occupation dating from the second and third quarter of the I century BC. Given the lack of studies on campanian ware of the Portuguese territory, a reexamining of the published data was made taking into account the typology of Jean Paul Morel. Though the available information is not yet representative, it may insight the distribution trends of the campanian ware. First: It might be possible that such a kind of ware could have arrived to the Portuguese territory only during the roman conquest, since the most ancient examples date back to the middle of the II century BC. Second: the distribution pattern suggests a strong linkage between the roman presence and the imports of this kind of wares, given the absence of evidence in the nordern territory until the middle of the I century BC. Third: two different, though contemporaries, channels of distribution can be found in the south : one along the shore, and the other confining to the continental areas from the low Guadiana valley. Some footnotes bring up-to-date the information, as this paper was delivered for publication in 1984.